Detection and quantification of alcohol compounds in food and beverages using static headspace-gas chromatography/mass spectrometry - Law, Se Vern (2012)
Foods serve as a basic requirement for human survival and play an important role in society from religious and cultural perspectives. In Islam, the cardinal rule is that any substance capable of intoxicating human when consumed is unlawful (haram) be it in small or large quantity.The objective of the present study wasto develop a standard method for quantification of ethanol and other alcohols using Static Headspace-Gas Chromatography/Mass Spectrometry (HS-GC/MS) in complex food matrices. The study also examined the ethanol contents from various types of food and beverage available atthe local market. Ethanol land higher alcohols in alcoholic beverages were also analyzed and quantified.An incubation temperature of 80 ºC for 15 minutes (for 5 mL of liquid samples) and 30 minutes for 5 g solid samples gave an optimum headspace extraction. The extraction efficiency of samples with different sugar, salt and acid concentrations were determined. Headspace xtraction efficiency showed no significant difference (p<0.05) between standard ethanol solution and solutions containing less than individually 5 % salt, sugar and acid. The method for determination of ethanol and higher alcohols contents in liquid and solid food samples using Static HS-GC/MS was also validated. For liquid samples, the internal standard calibration method was used and linearity (r >0.99) in the range from 5 to 4,000 μg/mL of ethanol was observed. Results obtained indicated that the method was reliable with good recoveries (an average of 99.3%) and relative standard deviation (RSD) < 5.2. The standard addition method was used in the quantification of ethanol from solid foods. Ethanol concentrations from samples were classified into four; trace, low, medium, and high. In this study, three spiked levels within the linearity range for each level were added tothe samples. The concentration of ethanol spiked into solid food samples ranged from 1 mg/kg sample to 5240 mg/kg sample. RSD of 2.39 and 3.94 were obtained for intraday and interday repeatability tests. A total of 154 samples including fermented foods,carbonated drinks, juices and cordials, tea and coffee, energy drinks, colouring and flavourings, vinegars and sauces were analyzed. Of the total number of samples screened, 106 were found to contain ethanol which ranged from 5 to 33919 ppm. Twenty-five commercial (industrially manufactured and taxed) and two home-made alcohol products in Malaysia were also collected and analyzed for volatile compounds. The quantification of higher alcohols including 1-propanol, 2-methyl-1-propanol, 2-methyl-1-butanol and 3-methyl-1-butanol were carried out. The concentrations of higher alcohols in alcoholic beverages ranged from 5 to 331 ppm. The presence of ethanol in a food product is either through fermentation or added as processing aid.The standard method for quantification of low ethanol concentration in a complex food matrix is crucial for the development of halal food analysis. The results of this study also provided a database of the ethanol contents in various foods and beverages. The presence of the other higher alcohols in khamris also highlighted.The issue of contamination of prohibited substances such as khamr has to be resolved through utilizing advanced scientific techniques as tools for inspection and analysis where even trace amounts of contamination is essential and crucial to assure that halal requirements are met. This will in turn increase competitiveness of Malaysian food exporters as well as protect the rights of consumers.